The construction of social imaginaries from the Nihonshoki: the late Asuka period and the beginning of Nara (672-720) - Vargas Alvarado, Víctor Julio (2024)
This work is based on the following general objective: Analyze the Nihonshoki as a product of its time—when it was commissioned by Emperor Tenmu (672-686) and completed in the year 720[1]—to compare its function in the construction of a social imaginary that united Japan at that time. In this way, it is considered the possible purpose that the text in question originally had, to legitimize the imperial house and that Tenmu's rise to power after the Jinshin War would not be questioned, trying to demonstrate with the text the divine origin of all the emperors and empresses so far, as well as Tenmu inserting himself into this lineage.   [1] Barnes, State Formation in Japan Emergence of a 4th-century ruling elite, 203.